Composição química e atividade antimicrobiana de óleos vegetais in natura e ozonizados em Acinetobacter baumannii - (:unkn) unknown (Universidade Brasil, 2021)
The study of infection control mechanisms caused by bacteria is a topic of interest to different professionals involved in the hospital environment. This work aimed to investigate the use of vegetable oils as an alternative treatment in the control of these infections. The bactericidal effect of canola, coconut and palm oil, in natura and ozonized oils, was evaluated under Acinetobacter baumannii, a species of bacteria that stands out as an important opportunistic pathogen and is responsible for infections related to the care of health. All the tested oil samples were characterized by the techniques of gas chromatography, I2 and peroxides index, the most altered characteristic under the effect of the ozonation process, passing from undetectable in the samples of in natura oils to the fractions 125,7 ± 0,2; 422,4 ± 0,2 and 434,8 ± 0,2 meq/Kg of Na2S2O3 for canola oil, coconut and ozonized palm oil. The reduction of microbial load in A. baumannii strains was 93,5, 71,6 and 85,9% for canola, coconut and in natura palm oils, respectively, and 96,2, 93,8 and 91,0% for the oils of canola, coconut and ozonized palm oil, respectively. In addition, the efficiency in the inhibition time of A. baumanni showed that ozonized oils present immediate bactericidal action, where their bacterial count in 10 min equates to the results of in natura oils after 30 min of incubation. These results revealed that the oils tested can be used in the control of bacterial infections and the ozonization of these oils potentiates the bactericidal action. The results showed, however, that the comparison between the microbial counts of in natura and ozonized oils did not point significant differences, since all the resulting p-values were higher than the level of significance adopted for the comparative test. A similar result was found in the comparison among ozonized oils in terms of microbial count, that is, there were no significant differences among microorganism counts when the different types of ozonized oils were compared.
Keywords: Acinetobacter baumannii; Ozônio; Atividade bactericida; Plantas medicinais; CS